Rock slope stability and excavatability assessment of rocks at the Kapikaya dam site, Turkey - Gurocak, Zulfu; Alemdag, Selcuk; Zaman, Musharraf M. (Elsevier, 2008)
This paper presents the slope stability and excavatability assessment of rocks at the Kapikaya dam site that contains diabases. Both field and laboratory studies were carried out. The field study involved detailed discontinuity surveys. Laboratory tests were carried out to determine uniaxial compressive strength, Young's modulus, unit weight, point load strength index and shear strength parameters of discontinuities. Kinematical and numerical analyses were performed to determine right and left slopes at the dam site. According to kinematical analyses, the types of planar and wedge failure are not expected at the site. Also, shear strength reduction analyses was carried out using Phase(2) for the right and left slopes at the dam site. According to results of numerical analysis, Strength Reduction Factor (SRF) of the right and left slopes are 8.08 and 6.5 respectively and any rotational failure will not occur. The excavation category of the diabases was determined as easy ripping for the right slope and easy-hard ripping for the left slope. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: excavatability; Kapikaya dam; kinematical analysis; rock slope stability; shear strength reduction analyses